Koebner phenomenon in epidermolysis bullosa acquisita: Letter to the editor - Kökçam, Ibrahim; Akpolat, Nusret (Turkiye Klinikleri, 2008)
[Abstract Not Available]
Keywords: adult; case report; clinical feature; epidermolysis bullosa acquisita; histopathology; human; human tissue; isomorphic phenomenon; letter; male; physical examination; skin biopsy; skin defect